Key Product Diary: Rice (India) - Nayak, Swati; Hossain, Sk Mosharaf; Tyagi, Neeraj Kumar; Nath, Anirban; Shukla, Sarvesh; Mohapatra, Subhasmita; Rout, Dillip Kumar; Swain, Girija Prasad; Singh, Varsha; Moharana, Rabindra; Nayak, Sampad Kumar (International Rice Research Institute, 2025)
This Product Diary is developed by IRRI-Seed System and Product Management Team to support seed multipliers and selling institutions for quick decision-making and strengthen linkages for early generation seeds from source breeding institutions